2017
DOI: 10.1177/0001839216686531
|View full text |Cite
|
Sign up to set email alerts
|

Labor of Love: Amateurs and Lay-expertise Legitimation in the Early U.S. Radio Field

Abstract: Many actors claim to be experts of specialized knowledge, but for this expertise to be perceived as legitimate, other actors in the field must recognize them as authorities. Using an automated topic-model analysis of historical texts associated with the U.S. amateur radio operator movement between 1899 and 1927, we propose a process model for lay-expertise legitimation as an alternative to professionalization. While the professionalization account depends on specialized work, credentialing, and restrictive jur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 101 publications
1
66
0
Order By: Relevance
“…These authors pursued this interest by analyzing the evolution of the U.S. wireless‐radio‐broadcasting industry, in which radio operators, or “hams” as they were called, went from being viewed as a nuisance to their knowledge being viewed over time as important to the profession and collaborating with professionals in the field, including top scientists and Nobel Prize winners. Croidieu and Kim (2018) used topic modeling, but unlike Almquist and Bagozzi (2019), focused on the temporal, evolutionary dynamics of the U.S. radio broadcasting industry.…”
Section: Examples Of Theorizing From Organizational Theory Using Qualmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors pursued this interest by analyzing the evolution of the U.S. wireless‐radio‐broadcasting industry, in which radio operators, or “hams” as they were called, went from being viewed as a nuisance to their knowledge being viewed over time as important to the profession and collaborating with professionals in the field, including top scientists and Nobel Prize winners. Croidieu and Kim (2018) used topic modeling, but unlike Almquist and Bagozzi (2019), focused on the temporal, evolutionary dynamics of the U.S. radio broadcasting industry.…”
Section: Examples Of Theorizing From Organizational Theory Using Qualmentioning
confidence: 99%
“…Such textual material was assumed to reflect the evolving perceptions of key actors in the early development of U.S. radio broadcasting. Unlike the previously described study, Croidieu and Kim (2018) analyzed the text over time to detect trends in the identified topics in relation to the evolving institutional context of the U.S. radio broadcasting industry at the beginning of the nineteenth century. They aimed to detect topical trends in order to describe the underlying mechanisms that led to the legitimizing of amateur radio operators as industry experts.…”
Section: Examples Of Theorizing From Organizational Theory Using Qualmentioning
confidence: 99%
See 3 more Smart Citations